1979
DOI: 10.1084/jem.150.3.432
|View full text |Cite
|
Sign up to set email alerts
|

Mouse alloantibodies capable of blocking cytotoxic T-cell function. I. Relationship between the antigen reactive with blocking antibodies and the Lyt-2 locus.

Abstract: In an attempt to produce allonatibodies to cytotoxic T-cell receptors, hyperimmune anti-lymphocyte antisera have been raised in mice of various strain combinations, and have been tested for their ability to block allogeneic cell-mediated lymphocytotoxicity (CML) in the absence of complement at the T killer cell level. Most of the sera failed to show any significant and reproducible inhibitory effects. However, among C3H anti-B10.BR antisera, some sera were found to be capable of significantly inhibiting CML. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(47 citation statements)
references
References 17 publications
4
43
0
Order By: Relevance
“…Anti-CD8 Abs have been used widely to investigate the role of CD8 in CD8 + T cell activation. Early studies showed that preincubation with anti-CD8 Abs can block conjugate formation between effector and target cells (16) and inhibit CD8 + T cell activation in response to cognate pMHCI presented on the target cell surface (17)(18)(19)(20). These findings provided key evidence that CD8 was important in the process of CD8 + T cell activation.…”
Section: D8mentioning
confidence: 51%
See 1 more Smart Citation
“…Anti-CD8 Abs have been used widely to investigate the role of CD8 in CD8 + T cell activation. Early studies showed that preincubation with anti-CD8 Abs can block conjugate formation between effector and target cells (16) and inhibit CD8 + T cell activation in response to cognate pMHCI presented on the target cell surface (17)(18)(19)(20). These findings provided key evidence that CD8 was important in the process of CD8 + T cell activation.…”
Section: D8mentioning
confidence: 51%
“…Anti-CD8 Abs are integral to the flow cytometric detection of pMHCI-restricted T cells and have been used extensively in the past to identify an important role for CD8 in CD8 + T cell activation (16)(17)(18)20). Most studies have concluded that anti-CD8 Abs inhibit the recognition of cognate Ag (19,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the specificity of the enzyme for the four different substrates (CDP, UDP, GDP and ADP) depends, in a parametric fashion, on the nature of effector ligands. Recent studies have shown that the Ly2 and UT4 molecules playa role in antigen recognition by T cells (Nakayama et al, 1979;Shinohara and Sachs, 1979;Swain et al, 1984). In the case of the Ly2 molecule, available data suggest that this molecule enhances the affinity of antigen binding, being essential when the T-cell receptor has a borderline affinity for antigen, but -not when the receptor has an intrinsically high affinity.…”
Section: Precedents For Multiple Complementarity Statesmentioning
confidence: 99%
“…Because of their selective expression on functionally distinct subpopulations, the macromolecule(s) carrying the Lyt-2 and Lyt-3 antigens have been thought to perform essential functions, most likely involving cellular interactions or recognition of antigen. Support for this idea has come from functional studies of cytotoxic effector T cells, in which antibodies to Lyt-2 or Lyt-3 were shown to block killing by binding to the effector cells (12,17). Ledbetter et al have reported the biochemical properties and cell surface distribution of T lymphocyte subpopulations of the homologue of Lyt 1, 2 and 3 antigens and Leu 1 and Leu 2 antigens, but the homologue of Leu 3 antigen in mice has not been identified (10).…”
Section: Discussionmentioning
confidence: 99%